Comments on "Parallel algorithms for hierarchical clustering and cluster validity - Murtagh, F. (IEEE transactions on pattern analysis and machine intelligence, 1992)
In the above-titled paper (ibid., vol.12, no.11, p.1088-92, Nov. 1990), parallel implementations of hierarchical clustering algorithms that achieve O(n/sup 2/) computational time complexity and thereby improve on the baseline of sequential implementations are described. The latter are stated to be O(n/sup 3/), with the exception of the single-link method. The commenter points out that state-of-the-art hierarchical clustering algorithms have O(n/sup 2/) time complexity and should be referred to in preference to the O(n/sup 3/) algorithms, which were described in many texts in the 1970s. Some further references in the parallelizing of hierarchic clustering algorithms are provided.< >